Alternative Assessments in Online Learning during Covid-19 Pandemic: The Strenghths and Weaknesses - Arifuddin, Ahmad; Turmudi, Turmudi; Rokhmah, Ummi Nur (International Journal of Elementary Education, 2021)
Currently, online learning becomes a new trend in the Indonesian education. But, the educators are not ready to adapt to online learning, especially in online learning assessments. This study aims to describe the alternative assessments in online learning that can be implemented at elementary education along with its advantages and disadvantages. This study employed a qualitative approach with the literature review method. Researchers collected a number of reputable national and international journal articles, textbooks, handbooks, regulations, and so on from the google scholar database, science direct, eric, and others related to research problems and objectives. The analysis of the literature review uses the critical appraisal method. The results of this study showed that online learning assessments that can be implemented in elementary education were formative and summative assessments. It included cognitive assessments, performance assessments, portfolios, writings and journals, self-assessment and peers-assessments. The use of online learning assessments has many advantages such as the availability to conduct tests on demand and at any time, provides direct feedback to users, the students’ quick access to the test results, and a more accurate measurement of student learning. However, online assessment systems also have several drawbacks, such as students who have low information technology (IT) skills might be disadvantaged. For this reason, in implementing online learning and assessment, teachers and students should master information and communication technology skills.